Evaluating the performance of unhealthy junk food consumption based on health belief model in elementary school girls - Azam Fathi; Gholamreza Sharifirad; Siamak Mohebi (Mashhad University of Medical Sciences, 2017)
Abstract Background and objective: Nowadays, due to changes in eating patterns, the worthless junk foods are replaced useful food among children. This study aimed to evaluate the performance of unhealthy junk food consumption based on health belief model in elementary school girls Methods: Cross-sectional study Descriptive-analytic type of multi-stage sampling (208 samples) was carried out in 2016. The survey instrument was a questionnaire valid and reliable based on the Health Belief Model (70 items). Data was analyzed by SPSS software according to statistical tests of significance level of 0.05. Results: Results showed that students of sensitivity (49%) and relatively high efficacy (53/8%), perceived benefits (73/1%) and better social protection (68/3%) had. The results showed that among all the health belief model structures with yield (junk food intake) significantly correlated. Also significant differences in parental education and sensitivity, perceived severity, self-efficacy, social support and yield (p<0/05). Conclusion: The results of this study showed that students from relatively favorable sensitivity and self-efficacy, perceived benefits and social protection in the field of unhealthy snacks were good. Also a significant relationship between structural and non-use study results showed unhealthy snacks but because of the importance of unhealthy snacks and unhealthy snack consumption among school children and the complications of the health belief model in predicting nutritional behaviors suggest that this model used as a framework for school feeding programs. Paper Type: Research Article.